Priapism in a Child from Homocystinuria from Methylenetetrahydrofolate Reductase MTHFR (C677T) Mutation - Ameer Kakaje; Ammar Fadel; Osama Hosam Aldeen; Othman Hamdan (Case Reports in Urology)
Priapism is a prolonged involuntary erection that can have severe complications if left untreated. Ischaemic priapism is very rare in children and requires urgent intervention to prevent permanent erectile dysfunction and penile shortening. It can be caused by ischaemia in sickle cell anaemia, leukaemia, trauma, drugs, or idiopathy. Homocystinuria is a rare autosomal recessive disorder that can cause hyperhomocysteinemia and hypercoagulability. Very few reports suggested that priapism can be caused by hyperhomocysteinemia, and they were in adults. However, we present the first of such a case to the best of our knowledge of a prepubescent child who only had the MTHFR (C677T) mutation that causes homocystinuria and had ischaemic priapism. A nine-year-old Syrian Arab boy was presented with priapism that lasted for a few hours. Blood tests show normal blood count, film, and haemoglobin electrophoresis. However, prothrombin time, partial thromboplastin time, homocysteine level, and C-reactive protein were elevated. Other coagulation tests were within the normal range. Doppler ultrasonography found decreased cavernous blood flow, and warm 0.9% saline lavage of the cavernosa was indicated and successfully treated the priapism. Genetic testing for the homozygous MTHFR (C677T) mutation was later confirmed, and warfarin was indicated. In conclusion, homocystinuria is very rare in priapism, and this is the first case to report this phenomenon in a child. Ultrasonography in low-income countries is an essential tool that helps identify a wide variety of medical conditions such as priapism and can be successfully managed by aspiration with warm saline.